Tracking Saudi EFL Students’ Reflections of Online Learning During Coronavirus: Different Rounds - Al Shlowiy, Ahmed (Frontiers in Education, 2021)
The sudden shift into online learning due to COVID-19 has produced many challenges and new educational approaches across all educational systems. Language learning systems were enforced to utilize fully remote education solutions. Responding to COVID-19 is a crucial investigation to find out the challenges, barriers, suggestions, concerns, and deficiencies of teaching English in Saudi Arabia. It also assists in developing the Saudi English as a Foreign Language (EFL) context in the future and support its students, teachers, and policymakers. This study tracks the influence of this shift on the EFL students in a Saudi high school. Data collection depends on reflective questions sent to the students through the survey and WhatsApp Group three times during the pandemic: April 2020, October 2020, and April 2021. The results show that students faced several threats, ambiguities, and deficiencies that are classified into: (a) students’ emotions, (b) learning environment, (c) student characteristics, and (d) deficiencies and needs. The students gradually acquired experience to deal with those issues and cope with their frustration. Then, they performed in either positive or negative ways depending on their acceptance of the online learning context. The study ends with some implications to efficiently use different virtual tools in the EFL context.